IL-1 and T Helper Immune Responses - Santarlasci, Veronica; Cosmi, Lorenzo; Maggi, Laura; Liotta, Francesco; Annunziato, Francesco (Frontiers in Immunology, 2013)
CD4 T cells play a critical role in mediating adaptive immunity to a variety of pathogens as well as in tumor immunity. If not adequately regulated, CD4 T cells can be also involved in autoimmunity, asthma, and allergic responses. During TCR activation in a particular cytokine milieu, naïve CD4 T cells may differentiate into one of several lineages of T helper (Th) cells, including Th1, Th2 and Th17, as defined by their pattern of cytokine production and function. IL-1, the prototypic proinflammatory cytokine, has been shown to influence growth and differentiation of immunocompetent lymphocytes. The differential expression of IL-1RI on human CD4 T cell subsets confers distinct capacities to acquire specific effector functions. In this review, we summarize the role of IL-1 on CD4 T cells, in terms of differentiation, activation and maintenance or survival.